Heat Shock Proteins 70 Regulate Cell Motility and Invadopodia-Associated Proteins Expression in Oral Squamous Cell Carcinoma - Ding, Le-Xi; Zhang, Jing; Yang, Si-Si; Wu, Jin; Su, Tong; Wang, Wei-Ming (Frontiers in Endocrinology, 2022)
Background Many studies have shown that diabetes is often closely related to oral squamous cell carcinoma (OSCC) occurrence and metastasis. Heat shock protein 70 (Hsp70) is a molecular chaperone related to diabetes complications. This study aims to investigate the role of Hsp70 in OSCC in expression of invadopodia-associated proteins. Methods The expressions and correlation of HSP70, Hif1α, MMP2, MMP14, and cortactin were examined using bioinformatics analysis and verified by OSCC tissue microarrays. Assay in vitro was performed to analyze cell migration capacity after treatment with or without the HSP70 inhibitor. Results The expressions of invadopodia-associated proteins were enhanced in OSCC tissues compared with paracarcinoma tissues and partially correlated with HSP70. Inhibiting HSP70 significantly decreased the cell viability, proliferation, and migration of OSCC cells. Conclusions HSP70 may be involved in invadopodia-associated proteins in OSCC cells, which provides a promising method for treatment of OSCC metastasis.